The Effect of Social Support, Emotional Intelligence and Self Efficacy on Career Adaptability - Bagus Cahyono; Qristin Violinda; Noni Setyorini (Value Management Research, 2024)
This study aims to determine the effect of social support, emotional intelligence and self-efficacy on career adaptability. This study used a probability sampling technique with a purposive sampling method. Data processing used the SPSS version 25 program. The population used in this study were final semester students at PGRI University Semarang and the sample used was 100 respondents from various study programs at UPGRIS. Primary data by distributing questionnaires via google form. The results of the analysis and discussion show that there is a positive and significant influence between the Social Support variable (X1) on the Career Adaptability variable (Y) partially, with t count 2.405 > t table 1.984 with a significance level of 0.018 <0.05. There is a positive and significant influence between the Emotional Intelligence variable (X2) on the Career Adaptability variable (Y) partially, with t count 2.448 > t table 1.984 with a significance level of 0.016 <0.05. There is a positive and significant influence between the variables Self-Efficacy (X3) Career Adaptability (Y) partially, with t count 6.503 > t table 1.984 with a significance level of 0.000 <0.05. There is a positive and significant influence between the variables Social Support (X1), Emotional Intelligence (X2) and Self-Efficacy (X3) on Career Adaptability (Y), with the F test results obtained an F value of 130,129 > F table 3.091 with a significance value of 0.000.